Weed management in broadcast sesame (Sesamum indicum L.) through sequential application of herbicides: WEED MANAGEMENT IN BROADCAST SESAME THROUGH SEQUENTIAL APPLICATION OF HERBICIDES - K SATHISH BABU; D SUBRAMANYAM (Journal of Oilseeds Research, 2018)
A field experiment was conducted to study the effect of sequntial application of pre-and post-emergence herbicides on growth, nutrient uptake and yield of broadcast sesame on sandy loam soils. Eleven weed management practices consisting of pre-emergence application of pendimethalin @ 750 g/ha, oxyfluorfen @ 75g/ha and oxadiargyl @ 75g/ha alone and sequential application ofthese pre-emergence herbicides followed by post-emergence application of quizalofop @ 50g/ha and propaquizafop @ 60g/ha including two hand weedings at 20 and 40 DAS and unweeded check were compared in randomized block design with three replications. Results revealed that the lowest density and dry weight ofweeds with lesser weed index were recorded in the plots treated with pre-emergence application of oxyfluorfen @ 75g/ha followed by quizalofop @ 50 g/ha applied at 20 DAS. The same weed management practice recorded significantly higher stature of growth parameters and yield attributes. The increase in seed yield of sesame was 38.0 per cent with sequential application of oxyfluorfen @ 75g/ha followed by quizalofop @ 50 g/ha applied at 20 DAS compared to unweeded check. Heavy weed infestation in unweeded check plots resulted in incresed weed nutrient uptake upto 44.6, 5.6 and 34.0 kg of N, P and K/ha, respectively. Oxadiargyl and oxyfluorfen @ 75 g/ha each showed phytotoxicity score of '4' and '3' respectively in 0 to 10 scale. Pre-emergence application of oxyfluorfen @ 75 g/ha followed by propaquizafop @ 60g/ha applied at 20 DAS recorded the highest benefit-cost ratio.